1996
DOI: 10.2175/106143096x127875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, empty bed contact time and hydraulic loading rate on lead removal by granular activated carbon columns

Abstract: Batch and column studies were performed to determine the effect of pH, empty bed contact time (EBCT), and hydraulic loading rate (HLR) on lead removal by granular activated carbon (GAC) columns. Lead removal increased with increasing pH, and for the majority of the adsorbate:adsorbent ratios investigated, was 100 % at pHs <

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The q 50% -capacity decreased for Zn from 2.25 mg/g to 0.42 mg/g (double influent concentration) and to 0.14 mg/g (double influent concentration and double flow-rate). These results indicated that the impact of the EBCT for calcium carbonate was comparable to the ones for GAC and manganese oxide-coated media [19,38]. Inglezakis et al [43] also determined for a zeolite that the breakthrough point (set at c/c 0 = 10%) could be observed after a smaller amount of treated bed volumes as the flow-rate increased and the EBCT decreased.…”
Section: Column Experimentsmentioning
confidence: 68%
See 2 more Smart Citations
“…The q 50% -capacity decreased for Zn from 2.25 mg/g to 0.42 mg/g (double influent concentration) and to 0.14 mg/g (double influent concentration and double flow-rate). These results indicated that the impact of the EBCT for calcium carbonate was comparable to the ones for GAC and manganese oxide-coated media [19,38]. Inglezakis et al [43] also determined for a zeolite that the breakthrough point (set at c/c 0 = 10%) could be observed after a smaller amount of treated bed volumes as the flow-rate increased and the EBCT decreased.…”
Section: Column Experimentsmentioning
confidence: 68%
“…Between pH 5 and 6 the capacity increased slightly, whereas it was several times higher for pH 7 compared with pH 6. Reed et al [38] [24], the pH value is at or above the point of zero charge that leads to negatively charged sorbent surfaces and higher retention of cations [23], and sorption also increases because metal ions exchange hydrogen ions of the sorbent surfaces more likely [39]. Thus, higher capacities for all six sorbents were expected for an initial pH value of 7 instead of 5.…”
Section: Batch Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Iron oxide coated meterials for heavy metal removal have been proved successful for the enhancement of treatment capacity and efficiency when compared with uncoated filter media, such as silica sand [10][11][12][13][14], granular activated carbon [15] and polymeric media [16,17]. For example, Edwards and Benjamin [7] found that coated media have similar properties to unattached coating materials in removing metals over a wide pH range, and that Fe oxide coated sand was more effective than uncoated sand.…”
Section: Introductionmentioning
confidence: 99%
“…Empty bed contact time (EBCT) is the residence time (in min) a fluid element is in contact with the bed, and is related to the systems' removal kinetics [35]. This is represented by the relationship between the bed depth (H) in the column and the feed solution velocity (v) [25,34], as given by:…”
Section: Packed Fixed-bed Column Design Considerationsmentioning
confidence: 99%